Aesthetic Sentence in the Novel Alun Samudra Rasa by Ardini Pangastuti: Stylistic Study - Winarsih, Winarsih; Dhoni Zustiyantoro (Centre for Literary and Cultural Studies, 2025)
This study aims to describe the aesthetic sentence patterns in the novel Alun Samudra Rasa as a characteristic of the linguistic aspect that affects the quality of the novel. This study uses Leech's stylistic approach to describe linguistic descriptions with aesthetic appreciation related to the object of study. The formulation of the problem in this study is how sentence patterns in novels can create aesthetic charm. This research is a qualitative study. Data were collected through heuristic, hermeneutic and bibliographic techniques, listening, taking notes, and analyzing the flowing model. This study's results indicate that sentence patterns create aesthetic characteristics in the novel, including parallelism sentence patterns, antithesis, inversion patterns, descriptive phrases, climax, anticlimax, and repetition. These sentence patterns are used because of the author's unique style and skill in processing sentences. These aesthetic sentence patterns seem to be related to each other; there are rhythmic sentence patterns, sentences that have a dramatic effect, changes in the SPOK (Subjek-Predikat-Objek-Keterangan) arrangement pattern, sentences complete of imagination, chronological order, distinctive repetition and the use of diction in sentences.